Value for Money from Public Education Expenditure on Elementary Education in India - World Bank Group (World Bank, Washington, DC, 2016)
The World Bank has been supporting the Universalization of Elementary Education (UEE)program for India through its support to the flagship program of the Government of India, theSarva Shiksha Abhiyan (SSA). The Bank's ongoing support to SSA is a little over $ 1 billion.With reducing national level budgetary allocation and scarcity of resources for publicly-fundededucation, it is important to analyse the efficiency and effectiveness of the investments in thesector. It is critical that financial investments made have been used efficiently and yield a highreturn in terms of children's access to education and learning outcomes. With this objective, the World Bank as a part of its ongoing support to SSA, undertook a Value for Money (VFM) analysis that could assess the returns from public education expenditure. This paper attempts to calculate and benchmark the economic value of any increases in children’s access to schooling and in students' learning levels that may result from increases in public education spending over time.